2011
DOI: 10.1111/j.1365-2966.2010.17900.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio-continuum detections of Galactic Planetary Nebulae - I. MASH PNe detected in large-scale radio surveys

Abstract: We present an updated and newly compiled radio‐continuum data base for Macquarie/AAO/Strasbourg Hα (MASH) planetary nebulae (PNe) detected in the extant large‐scale ‘blind’ radio‐continuum surveys [NRAO VLA Sky Survey (NVSS), Sydney University Molonglo Sky Survey/Molonglo Galactic Plane Surveys (SUMSS/MGPS‐2) and Parkes‐MIT‐NRAO (PMN)] and, for a small number of MASH PNe, observed and detected in targeted radio‐continuum observations. We found radio counterparts for approximately 250 MASH PNe. In comparison wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
(91 reference statements)
1
22
0
Order By: Relevance
“…In particular, we used the list of NVSS radio continuum detections (Condon & Kaplan 1998) coincident with sources in the Strasbourg-ESO Catalog of Galactic Planetary Nebulae (Acker et al 1992), and in subsequent optical surveys (Luo et al 2005). Furthermore, we used the PNe from the the new Macquarie/AAO/Strasbourg Hα (MASH) catalog (Parker et al 2006;Miszalski et al 2008) detected at centimeter wavelengths in the NVSS and the Molonglo Galactic Plane Survey (MGPS-2; Murphy et al 2007), reported by Bojičić et al (2011). Other PNe with radio continuum observations reported elsewhere (Aaquist & Kwok 1990;Van de Steene & Pottasch 1993, 1995Van de Steene & Jacoby 2001) were also included in our list.…”
Section: Notesmentioning
confidence: 99%
“…In particular, we used the list of NVSS radio continuum detections (Condon & Kaplan 1998) coincident with sources in the Strasbourg-ESO Catalog of Galactic Planetary Nebulae (Acker et al 1992), and in subsequent optical surveys (Luo et al 2005). Furthermore, we used the PNe from the the new Macquarie/AAO/Strasbourg Hα (MASH) catalog (Parker et al 2006;Miszalski et al 2008) detected at centimeter wavelengths in the NVSS and the Molonglo Galactic Plane Survey (MGPS-2; Murphy et al 2007), reported by Bojičić et al (2011). Other PNe with radio continuum observations reported elsewhere (Aaquist & Kwok 1990;Van de Steene & Pottasch 1993, 1995Van de Steene & Jacoby 2001) were also included in our list.…”
Section: Notesmentioning
confidence: 99%
“…The small, low-excitation core is only ∼6 ′′ × 4 ′′ across, is nitrogen enriched (Vázquez et al 1998), and has an integrated flux, F (Hα) = 2.4 × 10 −13 erg cm −2 s −1 (López et al 2000). In addition, the compact core (but not the giant outflow) is detected in the radio at 6 cm (Bojičić et al 2011a). We plot the nebular core in Fig.…”
Section: A1 Backgroundmentioning
confidence: 99%
“…The extinction constants are usually determined from the Balmer decrement, as derived from optical spectroscopy, or by comparing the Balmer and radio continuum fluxes. To be as homogenous as possible, we re-calculated the radio-Hα extinctions using the radio data and methods given in Bojičić (2010) and Bojičić et al (2011aBojičić et al ( , 2011b, and references therein).…”
Section: Extinction Constantsmentioning
confidence: 99%
“…This sequence is similar to the order of FWZPs (Figure 11 Acker et al (1992) classified this source as a possible PN, which is a faint object highly reddened showing a weak H-alpha emission. Kohoutek (2001) and Bojičić et al (2011) also designated this source as PN in an extensive radio-continuum survey. However, the possibility of being a PN seems to be low because the SiO maser emission is not detected from a PN.…”
Section: Maser and Infrared Properties Associated With A Post-agb Stamentioning
confidence: 99%